Lamb feeding experiments - Menzies, C.S.; Erhart, A. (Kansas Agricultural Experiment Station, 2011)
Delivery of 602 fine-wool feeder lambs was accepted at Menard, Texas, October 16, 1963. They were sorted from 700 lambs and averaged 67.3 lbs. each with a 3% shrink. Purchase price was $16.25 per cwt. Immediately 197 were injected (intramuscular) with ½ cc. of an emulsified solution supplying 250,000 I.U. of Vitamin A, 37,500 I.U. Vitamin D, and 25 I.U. of Vitamin E. All lambs were shorn (average fleece, 3.7 lbs.) and then shipped to Garden City on a triple-deck truck. They arrived at the Experiment Station at 8 a.m. October 18, having lost approximately 4lbs. per lamb in transit. Lams were weighed on arrival, divided into pens of approximately 50 head each and fed about 40 lbs. of medium quality ground alfalfa hay and 45 to 60 pounds of green chopped grain sorghum stubble per lot until October 22 when they were moved to buffalo pasture. November 4 they were placed in dry lot and fed alfalfa hay and chopped sorghum stubble ration until started on test.
Keywords: Lambs; Vitamin A; Vitamin D; Vitamin E; Alfalfa